INVESTIGATING CONTRIBUTING FACTORS TO COMPREHENSION DIFFICULTIES AMONG YOUNG READERS - Honest Ummi Kaltsum; Shella Herliana; Sinta Diah Ayu Pitaloka (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study aims to identify factors contributing to reading comprehension difficulties in elementary school students. This study used a qualitative approach, with data obtained through interviews with students and teachers, as well as Focus Group Discussions (FGDs). Data were analyzed using the Miles and Huberman interactive analysis model, which includes the stages of data reduction, data presentation, and drawing conclusions. The results show that from the student perspective, reading comprehension difficulties are mainly caused by limited vocabulary, dependence on external assistance such as teachers or parents, difficulty understanding long texts comprehensively, and the use of ineffective reading strategies. From the teacher’s perspective, dominant factors include low interest in reading, difficulty concentrating, the impact of the Covid-19 pandemic which limits learning interactions, lack of parental guidance, and minimal motivation from the school. Teachers also highlighted limited mastery of new vocabulary, difficulty understanding complex sentences, being easily distracted, certain physical limitations, an unconducive learning environment, and inadequate facilities and infrastructure, such as libraries and reading corners. Meanwhile, the FGD results emphasized the importance of strategic solutions, such as fostering early reading habits, creating a literacy-rich environment, utilizing interactive media, providing motivation and rewards, integrating literacy-based learning models, and collaborating with parents and the community. Thus, this study concluded that reading comprehension difficulties are multidimensional and require comprehensive and collaborative interventions involving students, families, schools, and the surrounding community.